A ΔSOC-based equalization strategy applied to industry. (15th December 2020) - Wang, Maonan; Chang, Chun; Ji, Feng
Abstract: The voltage-based equalization strategy is widely used in the industry because the voltage ( U ) of the battery cell is very easy to obtain, but it is difficult to provide an accurate parameter for the battery management system (BMS). This study proposes a new equalization strategy, which is based on the difference between the state of charge (SOC) of any two battery cells in the battery pack, that is, a Δ SOC -based equalization strategy. The new strategy is not only as simple as the voltage-based equalization strategy, but it can also provide an accurate parameter for the BMS. Simply put, using the relationship between the open circuit voltage and the SOC of the battery pack, the proposed strategy can convert the difference between the voltage of the battery cells into Δ SOC, which renders a good performance. Additionally, the required parameters are all from the BMS, and no additional calculation is required, which makes the strategy as simple as the voltage-based balancing strategy. The four experiments show that the relative errors of Δ SOC estimated by the Δ SOC -based equalization strategy are 0.37%, 0.39%, 0.1% and 0.17%, and thereby demonstrate that the Δ SOC -based equalization strategy proposed in this study shows promise in replacing the voltage-based equalization strategy within the industry to obtain better performance.